A Probability Method for the Solution of the Telegraph Equation with Real-Analytic Initial Conditions - Samoilenko, I. V.; Turbin, A. F. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We propose a method for the construction of an analytic solution of the Cauchy problem for the telegraph equation that is based on its simulation by a one-dimensional Markov random evolution.